2011
DOI: 10.1016/j.cej.2010.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Binding mechanisms and QSAR modeling of aromatic pollutant biosorption on Penicillium oxalicum biomass

Abstract: a b s t r a c tThe biosorption of eight aromatic compounds with different functional groups by Penicillium oxalicum biomass were investigated. The affinity of the biomass for the eight compounds at pH 6.0 follows the following trend: 1-naphthalenamine > naphthol > benzoic acid > p-toluidine > p-cresol > p-toluic acid > phenol > p-toluenesulfonic acid. Biomass surface was characterized, and it was found that four discrete binding sites, corresponding to carboxyl (pK a = 4.0), phosphoric (pK a = 7.0), amine (pK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The peaks at 2925 and 2850 cm À1 indicated the aliphatic CAH stretch vibrations of the CH, CH 2 , and CH 3 groups. The peaks for amide bands were observed at 1654 cm À1 (amide I band), 1537 cm À1 (amide II band), and 1453 cm À1 (amide III band) [14]. The peaks at 1408 and 1384 cm À1 corresponded to the carboxylic acid and carboxylate ions on the biomass surface, respectively.…”
Section: The Change Of Surface Morphology and Functional Groups On Bimentioning
confidence: 95%
“…The peaks at 2925 and 2850 cm À1 indicated the aliphatic CAH stretch vibrations of the CH, CH 2 , and CH 3 groups. The peaks for amide bands were observed at 1654 cm À1 (amide I band), 1537 cm À1 (amide II band), and 1453 cm À1 (amide III band) [14]. The peaks at 1408 and 1384 cm À1 corresponded to the carboxylic acid and carboxylate ions on the biomass surface, respectively.…”
Section: The Change Of Surface Morphology and Functional Groups On Bimentioning
confidence: 95%
“…Several studies have found correlations between adsorption capacity and decreasing water-solubility of the sorbate Girgis 1998, 2003;Nouri et al 2002b;Dąbrowski et al 2005;Wu and Yu 2006a;Aktar et al 2007a;Hamdaoui and Naffrechoux 2007a;Thuy et al 2008;Navarro et al 2009;Hansen 2010;Zhang et al 2011c). An example is shown in Fig.…”
Section: Solubility Of the Sorbate Molecules In Watermentioning
confidence: 99%
“…As shown by Kumar and Min (2011b), fungal biomass may contain significant amounts of nitrogen in the form of amines and amides; this is attributable to the presence of protein. Various researchers have evaluated fungal material relative to the uptake of phenols and other synthetic organic compounds from solution (Young and Banks 1998;Rao and Viraraghavan 2002;Denizli et al 2005;Wu and Yu 2006b;Kumar et al 2009b;Pernyeszi et al 2009;Huang et al 2010;Kumar and Min 2011b;Zhang et al 2011c;Farkas et al 2013). Rao and Viraraghavan (2002) found the highest uptake following pretreatment of Aspergillus niger with sulfuric acid.…”
Section: Fungal Sorbent Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a review of the related literature, biosorption of organic compounds depends on various factors (molecular size, degree of ionization, solubility, charge, hydrophobicity [34]. 18.7% of sulfamethoxazole, sulfamonomethoxine and sulfadimethoxine were respectively biosorbed at pH 7, for 2.56 g.L -1 of activated sludge.…”
Section: Biosorptionmentioning
confidence: 99%